Petrology and Geochemistry of Volcanic Rocks of Kaba Volcano, Bengkulu - Muhammad Eval Juni Wijaya; Sakila Gia Mentari; Ridho Ramadhan Pratama; Victor Ranson Sitohang (Journal of Earth and Marine Technology (JEMT), 2025)
Mount Kaba is an active stratovolcano in Bengkulu Province, Indonesia, characterized by explosive magmatic eruptions and the presence of monogenetic volcanic centers, reflecting complex magmatic processes. This study focuses on the northern sector of the Mount Kaba area to investigate magma evolution and its relationship to volcanic development and hazard mitigation. Fifteen representative lava and pyroclastic rock samples were analyzed using petrographic observations and ICP-MS geochemical methods to determine major, trace, and rare earth element (REE) compositions. Petrographic results indicate basaltic to andesitic rocks with hypocrystalline textures, dominated by plagioclase, pyroxene, olivine, hornblende, and displaying porphyritic, trachytic, sieve, zoning, intersertal, and reaction rim textures that reflect disequilibrium processes and multi-stage magma evolution. Geochemically, rocks range from basanite/tephrite to dacite and belong mainly to calc-alkaline to high-K calc-alkaline magma affinities, forming two magma groups (Danau Mas and Kaba). Major element Harker diagrams show decreasing MgO, CaO, FeO, TiO₂ with increasing SiO₂ and increasing Na₂O + K₂O, indicating progressive differentiation. Trace element diagrams display positive trends of LILE and HFSE with SiO₂ and dual magma trends, suggesting multiple differentiation histories. Spider diagrams reveal LILE enrichment, HFSE depletion, and LREE enrichment relative to HREE, consistent with subduction-related magma sources. Integration of petrographic and geochemical data indicates that magma evolution was dominated by fractional crystallization, with additional influences from assimilation and magma mixing that produced compositional diversity and disequilibrium textures. Overall, the Mount Kaba magmatic system reflects a dynamic subduction zone environment characterized by multiple magma sources, progressive differentiation, and complex interactions within the crust, with implications for understanding volcanic processes and hazard potential in the northern sector.